Application of the Main Components Method for GNSS Interference Suppression - A. V. Nemov; Le. M. Dang; D. Yu. Tyuftyakov (Известия высших учебных заведений России: Радиоэлектроника)
In this paper three methods of interferences nulling for GNSS GPS or GLONASS are described. A digital antenna array for compensation of interferences is implied. Two methods are based on the eigenvector decomposition of the correlation matrix of received oscillations. An expansion of the correlation matrix on its eigensystem is applied. The eigenvector matrix must be divided on the noise and signal subspaces. Some main components of the eigenvector matrix are used to weight vector calculation. The structure of a space-time interferences compensator is shown. The comprehensive test and the comparative analysis of effectiveness of described methods with the classic gradient method of output fluctuation power minimize under restriction on radiation pattern are completed. A suppression coefficient ranges up to 60 dB.